Engineering of metal–organic framework nanomaterials on long-period fiber grating for acetone vapor sensing. Issue 52 (25th November 2022) - Wang, Haishi; Deng, Guowei; Dong, Lianghai; Zhao, Ke; Chen, Kaixin; Chiang, Kin Seng; Wu, Jieyun
Abstract : The long-period fiber grating was functionalized with metal–organic framework nanomaterial ZIF-8 for sensitive acetone vapor sensing with large dynamic range and fast response. Abstract : Metal–organic framework (MOF) material is one of the most promising porous nanomaterials for volatile organic compound (VOC) adsorption and sensing. The large surface area and the high porosity of MOF contribute to the high sensitivity of MOF-based VOC sensors. In this study, we engineer the coating of the zeolitic imidazolate framework material ZIF-8 grown on the surface of a long-period fiber grating (LPFG) for acetone vapor sensing. Being a periodic structure formed in a single-mode optical fiber, an LPFG is designed to couple light from the core to the cladding of the fiber at a specific resonance wavelength. Adsorption of acetone vapor molecules in the framework of the ZIF-8 coating can change the refractive index of the coating and cause a shift in the resonance wavelength of the LPFG. The sensitivity of the resonance shift of the LPFG to the acetone vapor concentration depends strongly on the thickness of the ZIF-8 coating. To create a dense ZIF-8 coating, at least five growth cycles of ZIF-8 (30 min growth for one cycle) are required, and nine growth cycles can create a 500 nm thick coating. The LPFG coated with nine growth cycles of ZIF-8 provides a high sensitivity of 21.9 nm ppm −1, a low detection limit of 1.4 ppm, and a wide detection range of about 1500 ppm. Our results can facilitate the development of high-performance optical fiber sensors based on MOF for VOC detection.